Iridium-Catalyzed Direct Cyclization of Aromatic Amines with Diols - Minakawa, Maki; Watanabe, Kouichi; Toyoda, Satoru; Uozumi, Yasuhiro (Synlett, 2018)
We developed an environmentally friendly iridium-catalyzed direct cyclization of aromatic amines with diols that generates the corresponding N-heterocyclic compounds with water as the sole by-product. Thus, under conditions of 165 °C for 18 hours, the direct cyclization of N-methylanilines with 1,3-propanediol by using an IrCl3 catalyst with rac-BINAP as a ligand in mesitylene afforded the corresponding tetrahydroquinoline derivatives with yields ranging from 73 to 83%. Under similar reaction conditions, direct cyclization of anilines with 1,3-propanediol produced the corresponding tetrahydrobenzoquinolizine derivatives with yields ranging from 26 to 76%.
Keywords: iridium catalyst; aromatic amines; diols; cyclization; N-heterocycles